Examining the Effects of Online Games on The Academic Performance of BPEd Students of Sultan Kudarat State University, Philippines - Lenny E. Cabrillos; Jegad D. Gapasin; Jeremy A. Marfil; Vivencio L. Calixtro Jr. (Universitas Pendidikan Indonesia (UPI), 2023)
During the COVID-19 pandemic, the rise in online gaming and the absence of face-to-face education in schools has raised worries about the effect on students' academic performance. This study aimed to find out the relationship between the level of online learning and the academic performance of BPEd students. It is in this light of this study to assess the level of impact of online games to the: (1) health aspect, (2) social aspect, (3) intellectual aspect, and (4) academic performance of chosen BPED students at Sultan Kudarat State University Access Campus. The researchers employed a descriptive-evaluative research approach since the study's findings would analyze students' engagement in online gaming applications, and the researchers used Google Forms to collect the data they required. With a total of thirty respondents, the set questionnaires employed will act as a data collection tool. Frequency count and weighted mean were the statistics employed in the investigation. According to the survey, the majority of the respondents are in the 20-year-old age group, with 40% of the respondents coming from the second-year level. It also revealed that the majority of respondents who played online games are men, accounting for 80 percent of the study's respondents. Based on the findings of this study, it can be concluded that playing online games has no substantial association with the respondents' academic success, as evidenced by their Probability-value.